Implementasi Program Unggulan Madrasah Dalam Pembentukan Life Skill Peserta Didik - Wiwin Setyowati (THE JOER: Journal Of Education Research, 2022)
The background of this research is as an effort to improve the quality of education because of the intense competition between schools to get students and the community, which in fact prefers institutions that can help students to be able to go straight into the world of work. The aim of the research in this thesis is to analyze the forms of the madrasa flagship program and to analyze the implementation of the madrasa flagship program in the formation of the life skills of students at the Kalimasada Integrated MA. The type of research used is qualitative research with a case study approach. Data collection techniques by way of observation, interviews, and documentation. The data analysis technique used in this qualitative research has four stages, namely data collection, data reduction, data presentation, drawing conclusions and verification. Whereas in looking for the validity or validity of the data using data triangulation techniques. The life skills program at the Kalimasada Integrated MA which has been made the flagship program of other madrasas in the Plandaan sub-district are the tahfidz, banjari, agriculture, carpentry, sewing, and computer programs. The results of the research show that the form of the life skill program is a form of product produced by students after participating in learning from the program. The orientation of the life skill program in this madrasah is that students have life skills, have an entrepreneurial spirit, can produce products that have selling points, are more independent and confident and are ready to compete in the world of work. The implementation of the madrasa flagship program in the formation of the life skills of students at the Kalimasada Integrated MA is carried out in accordance with the stated goals, namely to equip students with life skills to be independent, have an entrepreneurial spirit, dare to face challenges, and think creatively and smartly.